(untitled) (Web of Teachers: Inderscience Research, 2026)
The article presents a theoretical study of the possibilities of integrating the ethnoecological principles of the Avesta — an ancient Zoroastrian text — into modern educational practices for the formation of the ethnoecological culture of youth. Based on a critical analysis of the ecological content of the Avesta and ethnopedagogic concepts, a theoretical model of their application in educational processes has been developed. The proposed model focuses on the classification of living beings, ethical standards of environmental management, and principles of environmental cleanliness as fundamental elements in forming ecological consciousness. Drawing on interdisciplinary approaches from ethnopedagogy, cultural studies, and environmental education, the article argues that the ethnoecological principles of the Avesta can serve as a solid foundation for promoting sustainable development and preserving cultural heritage in modern education. The theoretical implications and potential applications of this model are discussed, with emphasis on its relevance in the context of global environmental challenges and the national educational policy of Uzbekistan.